Using dung bolus diameter for age estimation in an unstudied elephant population in Udzungwa Mountains, Tanzania - Katarzyna Nowak; Trevor Jones; Phyllis Lee (Pachyderm)
Savannah elephants make extensive use of montane forest in three Tanzanian massifs, including the highly biodiverse Udzungwa Mountains. We have begun the first study of the Udzungwa elephant population, which is perceived to be increasing and is compressed due to loss of connectivity with adjacent protected areas. Meanwhile, human-elephant conflict outside the forests is escalating. We tested a non-invasive technique for estimating elephant age from dung bolus diameter using a predictive equation derived from known-age elephants in Amboseli National Park, Kenya. Our results from 137 measurements of intact boli found an overall mean dung bolus diameter of 11.0 cm ± 2.1 and a mean age of 16.0 years ± 5.6, suggesting that the Udzungwa population is young but contains reproductive-age adults (>10 yrs old). This method’s precision and accuracy require further testing and we discuss the limitations; however, it has potential as a monitoring tool for elephant populations inhabiting forest elsewhere in Tanzania, and across Africa. We intend to re-run this analysis using a larger sample size from more sites, as well as incorporate elephant monitoring into the Udzungwa Mountains National Park’s long-term management plan.